An Ergonomic Flexible Girdle Design for Preteen and Teenage Girls with Early Scoliosis (Journal of Fiber Bioengineering and Informatics, 2014)
Adolescent Idiopathic Scoliosis (AIS) is a three-dimensional (3D) deformity of the spine that can occur inchildren aged 9 and older. It is more commonly found in girls. This paper presents an ergonomic flexiblegirdle or brace design for preteen and teenage girls who have early scoliosis with a spinal curve that is lessthan 20 degrees, which reduces the chances of further aggravation of their scoliosis by exerting correctiveforces onto their torso and improving their posture. During the design and development process, itwas found that the key factors that affect the efficiency of the flexible girdle are the design and fit ofthe garment, corrective force mechanism employment, material selection and application, and aestheticand convenience of the product that affect compliance. The results of ergonomic design process in thisproject can be applied to related product development projects in the future and used as reference fordoing so.
Keywords: Ergonomic Garment Design; Flexible Girdle; Scoliosis